2009
DOI: 10.1007/s10661-009-1146-8
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal uptake and its effect on macronutrients, chlorophyll, protein, and peroxidase activity of Paspalum distichum grown on sludge-dosed soils

Abstract: This study assessed the heavy metal (Cr, Mn, Ni, Cu, Zn, and Pb) uptake and its effect on biochemical parameters in Paspalum distichum, a wetland plant. Sludge collected from Bhalswa waste dump, New Delhi, was used as heavy metal source and dosed in different proportions viz. 20%, 40%, 60%, and 80% to the garden soil. The plants accumulated metals mostly in belowground organs. The metal accumulation followed the order: Cr>Mn>Cu>Zn>Ni>Pb. The range of heavy metal concentration in tissue of belowground organs af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…The pH of the sludge-amended soil of this study was neutral, but at the rhizosphere zone, acidic root exudates, or change in soil physicochemical condition can activate the metals from this fraction (Bhattacharya, Chakraborty, and Banerjee 2010). According to Tessier, Campbell, and Bisson (1979), under reductive conditions, the iron (Fe)-manganese (Mn) oxide-bound fraction can be released, whereas the organically bound metals may be released by the decomposition of organic matters by microorganisms.…”
Section: Discussionmentioning
confidence: 88%
“…The pH of the sludge-amended soil of this study was neutral, but at the rhizosphere zone, acidic root exudates, or change in soil physicochemical condition can activate the metals from this fraction (Bhattacharya, Chakraborty, and Banerjee 2010). According to Tessier, Campbell, and Bisson (1979), under reductive conditions, the iron (Fe)-manganese (Mn) oxide-bound fraction can be released, whereas the organically bound metals may be released by the decomposition of organic matters by microorganisms.…”
Section: Discussionmentioning
confidence: 88%
“…However, metal content in plant tissues should be measured in future studies to confirm this hypothesis. The weed could work as potential phytoremediator of water metal pollution due to both its ability to take up metals and its tolerance to high metal concentrations, as other studies have shown (Shu et al ; Paz‐Alberto et al ; Bhattacharya et al ).…”
Section: Discussionmentioning
confidence: 94%
“…The sludge compost used in the study contained nutrients such as organic matter, nitrogen, and phosphorus, which provide microorganisms with material rich in nutrients and energy, and consequently improve microbial activity and diversity. Nevertheless, the sludge compost also had high EC and levels of heavy metals, which would increasingly accumulate with higher sludge compost dosages, so that the higher sludge compost amendment may result in environmental stresses (Brookes 1995;Bhattacharya et al 2010;Wu et al 2012) and adverse effects on microorganisms. The PCA of carbon source utilization pattern showed that the ability of the soil microbial communities to catabolize the β-methyl-D-glucoside, L-asparagine, L-serine, α-cyclodextrin, γ-hydroxybutyric acid, and itaconic acid increased up to a sludge compost amendment dosage of 45 % and then decreased above 45 %.…”
Section: Discussionmentioning
confidence: 99%
“…Composting, which can eliminate pathogens, reduce metal availability, stabilize organic matter and produce an aesthetically acceptable product for use in agriculture, is regarded as an effective and environmentally sound procedure prior to the application of sewage sludge to soil (Curaqueo et al 2014;Zafari and Kianmehr 2014). However, heavy metals are non-biodegradable and accumulate in soil following amendment with sewage sludge compost, which represents a long-term environmental risk (Bhattacharya et al 2010;Nogueirol et al 2013). Sludge compost application to ornamental plants in gardens, greenbelts, or pots has advantages by reducing the potential risk of heavy metals and toxic organic compounds entering the human food chain (Silva et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation